SURGICAL OUTCOMES OF LAPAROSCOPIC HEPATECTOMY FOR HEPATOCELLULAR CARCINOMA: A SINGLE-CENTER EXPERIENCE (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of laparoscopic hepatectomy in the treatment of hepatocellular carcinoma at a single center.Methods: A descriptive study with retrospective and prospective data collection was conducted on 280 patients with hepatocellular carcinoma who underwent laparoscopic hepatectomy at Nghe An Oncology Hospital from January 2020 to May 2025. Variables included clinical characteristics, liver function (Child-Pugh classification), AFP levels, surgical characteristics, intraoperative and postoperative complications, length of hospital stay, and overall survival. Data were collected from medical records and postoperative follow-up and analyzed using SPSS 22.0.Results: The mean age was 65.2 ± 14.3 years, with a male-to-female ratio of 3.2:1. Most patients had Child-Pugh A liver function (96.8%), and AFP levels were mainly between 20-400 ng/mL (47.5%). Pure laparoscopic hepatectomy was performed in 93.9% of cases. Minor hepatectomy accounted for 60.3%, with posterior sectionectomy being the most common (16.7%). Major hepatectomy accounted for 39.5%, including left hepatectomy (19.3%), right hepatectomy (13.9%), and central hepatectomy (6.9%). The mean operative time was 116 ± 35.7 minutes, and the mean blood loss was 235 ± 73 mL. The rates of no complications were high both intraoperatively (94.7%) and postoperatively (92.5%), with bile leakage being the most common postoperative complication (3.2%). The mean hospital stay was 7.8 ± 1.4 days. The mean overall survival was 46.8 ± 1.5 months.Conclusion: Laparoscopic hepatectomy is a safe and feasible procedure with favorable outcomes for hepatocellular carcinoma and can be effectively applied in experienced centers with appropriate patient selection
Keywords: Laparoscopic hepatectomy, hepatocellular carcinoma, minimally invasive surgery, surgical outcomes.